O uso de analogias no ensino de Biologia: uma análise na literatura dos últimos 20 anos. - SOUSA, Vanuzia Melo de (2024)
This article aims to analyze how analogies are present in biology teaching in the last two decades. Through a bibliographic survey using Google Scholar based on data. Thus, 18 scientific publications were identified, with publications focusing on the analysis of educational materials being the most significant. The works point to a low level of instrumentation for teachers in the use of analogies and the need to include training in both initial and continuing teacher training. And it recommends caution regarding the direct use of analogies contained in didactic collections, as analyzes demonstrate that not all criteria for a good construction of an analogy are observed in these materials. This fact requires critical analysis, contextualization and analysis for good application. In short, studies with analogies in biology teaching have become more frequent in the last seven years and this fact may be related to the demands for methodological adaptations necessary to the context of the inclusive classroom, although this is not presented explicitly in the publications.